(3edNUGJ GdOQhS h JeGQjf eMdhdI (B: (3GdLRA GdChds - (3SYjOI(B, (3HhSYOIs ((3GdLRGFQ(B:s (3OGQ gheI(B,s, 2017)
(3ebOeI aj GdJMdjd GdGbJUGOj h GdeTcdI GdGbJUGOjI, GdWdH h GdYQV h GdJhGRf, bjGS GdehGRfGJ, JWHjbGJ Ydi JhGRf GdShb, JMdjd Sdhc GdeSJgdc(B/(3fXQjI GdefaYI,JMdjd Sdhc GdeSJgdc(B/(3fXQjI efMfjGJ GdShGA(B.s
(3eQGLY U(B.156s
Keywords: (3GdGbJUGO GdJMdjdjs; (3GdGbJUGO GdLRFjs